PEMBERDAYAAN PETANI KOPI SAJANG MELALUI EDUKASI PEMBUATAN PESTISIDA NABATI UNTUK MENGENDALIKAN HAMA KOPI PADA PERKEBUNAN KOPERASI BUMI TANI LESTARI INDONESIA - Suliartini, Ni; Wijayanti, Nabila; Sartika, Dini; Septianti, Nadia; Salafy, Musthofa; Ainurrahmah, Ayu; Jaya, Andika; Aliansyah, Micko; Toyyibah, Zurriatun; Firdaus, Egi; Wulandari, Alisa (Universitas Mataram, 2025)
Desa Sajang in the Sembalun District, East Lombok, is known as a coffee-producing center; however, farmers often face serious pest attacks. The use of synthetic pesticides can cause negative impacts on health and the environment, including soil and water contamination. Therefore, this activity aims to empower coffee farmers through education on the production of environmentally friendly botanical pesticides. The method used includes socialization through extension and demonstrations involving members of the Bumi Tani Lestari Indonesia Cooperative. This activity successfully increased farmers' knowledge of botanical pesticides by 40% after participating in the extension and practical sessions. Furthermore, farmers showed high interest in applying these techniques in their farming practices. They also began to understand the importance of shifting to safer and more sustainable natural materials for pest control. Through this activity, farmers are expected to reduce their dependence on chemical pesticides and adopt healthier, more sustainable farming practices. This activity successfully enhanced farmers' understanding and skills in environmentally friendly pest control.